Células-tronco mesenquimais em gel de plasma rico em plaquetas associados com microfraturas no tratamento de lesões condrais articulares em equinos - Yamada, Ana Lúcia Miluzzi [UNESP] (2015)
Several methods of cell therapy, such as mesenchymal stem cells (MSC) associated with platelet rich plasma (PRP), have been commonly used in the treatment of chondral articular defects and osteoarthritis, with satisfactory outcomes. Nowadays, the literature already shows an amount of positive features inherent to the MSC and the PRP. The use of cell therapy in association with other kinds of treatment, such as microfractures, allowed the researchers come closer to the ideal results. Thus, this study aimed to compare the clinical response and joint inflammation, the morphology and the structure of repair tissue from chondral defects experimentally induced in horses which were treated with microfractures, MSC, PRP alone or in combination of treatments. For this purpose, a first arthroscopic surgery was performed in 12 horses, which was considered time zero of the experiment (T0). A chondral defect of 15 mm diameter was created on medial femoral trochlea of both hindlimbs. The 24 patellofemoral joints of these animals were divided into four groups. The chondral defect was treated according to the group: GA: received treatment only with microfractures. GB received treatment with microfractures associated with MSC in PRP-gel scaffold. CG received treatment only with MSC in PRP-gel, and the GD was the control group, without treatments. MSCs were obtained from adipose tissue and PRP gel was obtained through double centrifugation method, followed by adding lyophilized bovine thrombin to achieve the gel consistency. The joints were followed during five months (T150) by clinical and laboratory assessment. At T150 there was performed a new arthroscopy aiming the macroscopic evaluation and repair tissue samples collection for histopathological, immunohistochemistry and qPCR analysis. We observed that the use of CTM in PRP-gel in the treatment of experimental chondral defects can modify the IL-1 and PGE2 concentrations in the synovial fluid. There ...